Cannabis use and transition to psychosis in individuals at ultra-high risk: review and meta-analysis. Issue 4 (16th November 2015) - Kraan, T.; Velthorst, E.; Koenders, L.; Zwaart, K.; Ising, H. K.; van den Berg, D.; de Haan, L.; van der Gaag, M.
Abstract : Background: Previous research has established the relationship between cannabis use and psychotic disorders. Whether cannabis use is related to transition to psychosis in patients at ultra-high risk (UHR) for psychosis remains unclear. The present study aimed to review the existing evidence on the association between cannabis use and transition to psychosis in UHR samples. Method: A search of PsychInfo, Embase and Medline was conducted from 1996 to August 2015. The search yielded 5559 potentially relevant articles that were selected on title and abstract. Subsequently 36 articles were screened on full text for eligibility. Two random-effects meta-analyses were performed. First, we compared transition rates to psychosis of UHR individuals with lifetime cannabis use with non-cannabis-using UHR individuals. Second, we compared transition rates of UHR individuals with a current DSM-IV cannabis abuse or dependence diagnosis with lifetime users and non-using UHR individuals. Results: We found seven prospective studies reporting on lifetime cannabis use in UHR subjects ( n = 1171). Of these studies, five also examined current cannabis abuse or dependence. Lifetime cannabis use was not significantly associated with transition to psychosis [odds ratio (OR) 1.14, 95% confidence interval (CI) 0.856–1.524, p = 0.37]. A second meta-analysis yielded an OR of 1.75 (95% CI 1.135–2.710, p = 0.01), indicating a significant association between current cannabis abuse or dependence and transition to psychosis. Conclusions: Our results show that cannabis use was only predictive of transition to psychosis in those who met criteria for cannabis abuse or dependence, tentatively suggesting a dose–response relationship between current cannabis use and transition to psychosis.